Optimizing Character Formation: Community Service to Improve Student Discipline at the Elementary School Level - Nurhayida Silalahi; Ester Julinda Simarmata; Rosdiana Samosir (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
This community activity attempts to enhance student discipline at the primary school level through a holistic strategy that engages kids, teachers, parents and the surrounding community. Starting with a successful opening seminar which introduced the concept of discipline as the main foundation in forming student character, this program continued with an interactive workshop which provided in-depth understanding and special training for teachers in integrating discipline habits into everyday learning. Involving parents and community people through discussion forums, this program enables successful collaboration between the school environment and the local community. Program evaluations reveal better understanding and good changes in student conduct. The closing seminar as the final event of the program provides an opportunity to present concrete outcomes, successful experiences and future visions. This community activity not only meets the goal of enhancing student discipline, but also fosters a communal commitment to maintain the culture of discipline that has been successfully developed. The outcomes not only have an influence at the school level, but also provide a successful model that may be replicated by other educational institutions in an effort to improve student discipline and the overall quality of basic education